2014
DOI: 10.1371/journal.ppat.1004060
|View full text |Cite
|
Sign up to set email alerts
|

A Neutralizing Anti-gH/gL Monoclonal Antibody Is Protective in the Guinea Pig Model of Congenital CMV Infection

Abstract: Human cytomegalovirus (HCMV) is the most common cause of congenital virus infection. Congenital HCMV infection occurs in 0.2–1% of all births, and causes birth defects and developmental abnormalities, including sensorineural hearing loss and developmental delay. Several key studies have established the guinea pig as a tractable model for the study of congenital HCMV infection and have shown that polyclonal antibodies can be protective [1]–[3]. In this study, we demonstrate that an anti-guinea pig CMV (GPCMV) g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Nevertheless, these data substantiate observational human cohort studies suggesting that maternal HCMV-specific antibodies decrease risk of placental virus transmission (20)(21)(22)36). Furthermore, these data affirm findings from the guinea pig model of congenital infection that demonstrate that preexisting antibodies (from either glycoprotein immunization or passive HIG/monoclonal antibody infusion) can reduce the incidence and/or severity of congenital guinea pig CMV infection (37)(38)(39)(40). The therapeutic efficacy of HIG in preventing placental transmission in mothers with primary HCMV infection is a topic of ongoing investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, these data substantiate observational human cohort studies suggesting that maternal HCMV-specific antibodies decrease risk of placental virus transmission (20)(21)(22)36). Furthermore, these data affirm findings from the guinea pig model of congenital infection that demonstrate that preexisting antibodies (from either glycoprotein immunization or passive HIG/monoclonal antibody infusion) can reduce the incidence and/or severity of congenital guinea pig CMV infection (37)(38)(39)(40). The therapeutic efficacy of HIG in preventing placental transmission in mothers with primary HCMV infection is a topic of ongoing investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Thus, it was concluded that a vaccine aimed at preventing congenital infection should contain PC. Finally, a neutralizing mAb to gH/gL was found to be protective in the guinea pig model of congenital infection [121]. However, concerns have been raised about the ability of the guinea pig model to predict the outcome of clinical trials [98,122].…”
Section: Development Of An Hcmv Vaccine: Potential Role Of the Pcmentioning
confidence: 99%
“…122 The proposed mechanisms of protection are virus neutralization, with proteins in the gH/gL/UL128/UL130/ UL131 complex being the major targets of neutralizing antibodies, reduction of placental inflammation and perhaps reduction in the cytokine-mediated cellular immune response. 123,124 Although antibodies play an important role in protection against CMV infection and disease, the level of protection is incomplete. 125,126 Notably, maternal preconceptional immunity fails to provide absolute protection against congenital HCMV infection, which is related to reinfection with a new HCMV serotype or reactivation of an endogenous virus.…”
Section: Antibody-mediated Immunity To CMV Infectionmentioning
confidence: 99%